2015
DOI: 10.1002/2014gl062247
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and CAPE dependence of rainfall extremes in the eastern United States

Abstract: We analyze how extreme rainfall intensities in the Eastern United States depend on temperature T, dew point temperature T d , and convective available potential energy CAPE, in addition to geographic sub-region, season, and averaging duration. When using data for the entire year, rainfall intensity has a quasi Clausius-Clapeyron (CC) dependence on T, with super-CC slope in a limited temperature range and a maximum around 25°C. While general, these features vary with averaging duration, season, the quantile of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
79
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 34 publications
9
79
0
1
Order By: Relevance
“…We alternatively calculated the temperature sensitivities for the daily rain rate, for the daily maximum temperature, as well as for the mean and maximum temperature of the day prior to event onset in order to exclude cooling due to the event itself, but the scaling results did not show significant differences to the results obtained from T mean . Similar low sensitivities against some variation in temperature choice were found by Lenderink and van Meijgaard (2009) and Lepore et al (2015).…”
Section: Datasupporting
confidence: 73%
“…We alternatively calculated the temperature sensitivities for the daily rain rate, for the daily maximum temperature, as well as for the mean and maximum temperature of the day prior to event onset in order to exclude cooling due to the event itself, but the scaling results did not show significant differences to the results obtained from T mean . Similar low sensitivities against some variation in temperature choice were found by Lenderink and van Meijgaard (2009) and Lepore et al (2015).…”
Section: Datasupporting
confidence: 73%
“…Statistical studies have confirmed the CC scaling in many regions of the world, especially for short-term precipitation (e.g., Blenkinsop et al 2015;Lepore et al 2015), although the temperature dependence of precipitation intensity is often higher than the CC rate (Lenderink and Meijgaard 2008;Lenderink et al 2011;Mishra et al 2012;Berg et al 2013), or negative at high temperature (Berg et al 2009;Maeda et al 2012). For Japan, Utsumi et al (2011) showed an approximate CC relation between temperature and extreme precipitation in some regions, except for a negative dependence above ~25°C.…”
Section: Introductionmentioning
confidence: 94%
“…To examine the true between precipitation intensity and local moisture supply, it is desirable to reduce the temporal resolution of observational measurements or to focus on individual events for the peak intensity. Based on hourly records from specific regions17181920, it is found that extreme precipitation has increased by nearly 14%/K, doubling that from the C-C argument and shown by daily data. Warming induced intensification of precipitation extremes is mainly associated with convective rainfall19.…”
mentioning
confidence: 94%